CROSS-CULTURAL COMPARISON OF LEXICAL INTENSIFICATION IN POLITICAL NEWS DISCOURSE (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article examines the cross-cultural features of lexical intensification in English and Uzbek political news discourse. The study investigates how journalists in both languages use intensifiers such as scalar adverbs, extreme adjectives, hyperbolic expressions, and culturally embedded evaluative units to shape ideological framing and influence audience perception. By comparing representative political news texts, the research identifies structural, semantic, and pragmatic similarities and differences in the use of intensified vocabulary. The findings show that English political discourse tends to employ graded lexical choices for subtle persuasion, whereas Uzbek discourse relies more heavily on emotionally charged and culturally resonant expressions. Overall, the analysis reveals how linguistic and cultural norms shape the communicative strategies of political media.